2020
DOI: 10.1002/rth2.12445
|View full text |Cite
|
Sign up to set email alerts
|

Compression stockings to prevent postthrombotic syndrome: Literature overview and presentation of the CELEST trial

Abstract: Postthrombotic syndrome (PTS) is a burdensome and costly complication of deep vein thrombosis (DVT) that develops in 20%‐40% of patients within 2 years after proximal DVT. In the absence of effective curative treatment, management of PTS relies on its prevention after DVT. The effectiveness of elastic compression stockings (ECS) to prevent PTS is uncertain. We present an overview of published studies assessing the efficacy of ECS to prevent PTS and present the protocol for the CELEST clinical trial. While prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…In the present study, compression stockings with a pressure range between 15 and 20 mmHg were used. The effective pressure of compression stockings varies by the product and with the disease -between 25 and 35 mmHg for deep vein thrombosis and between 18 and 35 mmHg for venous ulceration [16,17]. Further studies are warranted to examine whether the pressure of compression stockings exerts different effects on nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, compression stockings with a pressure range between 15 and 20 mmHg were used. The effective pressure of compression stockings varies by the product and with the disease -between 25 and 35 mmHg for deep vein thrombosis and between 18 and 35 mmHg for venous ulceration [16,17]. Further studies are warranted to examine whether the pressure of compression stockings exerts different effects on nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…47 48 Regarding study design, given the high risk of a placebo effect in PTS studies, we opted for a doubleblind design. 49 Our sample size could be perceived as Open access modest. However, based on our careful literature review, we hypothesise that there will be a 50% improvement in the primary study outcome in the MPFF arm, compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Among 96 patients who wore ECS, 30 (31%) developed PTS after 2 years of follow-up, while the incidence of PTS in patients without ECS was as high as 70%. Recent studies [61][62][63] have shown relatively consistent results in that wearing compression stockings providing a pressure of 30-40 mmHg after a diagnosis of thrombosis could halve the incidence of PTS after 2 years (from approximately 50.0% to 24.5%). However, a recent 64 randomized placebo-controlled trial involving 806 patients with DVT at 24 centers in the United States and Canada yielded opposite results.…”
Section: Optimal Treatment: Anticoagulant or Nonanticoagulantmentioning
confidence: 96%